Ticagrelor or prasugrel in patients with acute coronary syndrome with off-hour versus on-hour presentation: a subgroup analysis of the ISAR-REACT 5 trial - Behnes, Michael; Lahu, Shqipdona; Ndrepepa, Gjin; Menichelli, Maurizio; Mayer, Katharina; Wöhrle, Jochen; Bernlochner, Isabell; Gewalt, Senta; Witzenbichler, Bernhard; Hochholzer, Willibald; Sibbing, Dirk; Cassese, Salvatore; et al. (Clinical research in cardiology, 2023)
To assess the efficacy and safety of ticagrelor versus prasugrel in patients with acute coronary syndrome (ACS) presenting during off- and on-hours.
Online veröffentlicht: 05. Juli 2022
Gesehen am 17.06.2024